MANAJEMEN PENGUNJUNG DALAM PELESTARIAN SITUS TAMANSARI - , Wahyu Astuti ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Pesanggrahan Tamansari (Water Castle) is one of the cultural heritage of Yogyakarta which is used as tourism destination. Its management is on the Kraton Yogyakarta as the owner of Tamansari. Its daily execution is, however, done by Tepas Kaprajuritan Wahono Sartokriyo which is currently led by KGPH. Hadiwinoto. The management only sells entrance ticket to Gapura Panggung, Gedong Sekawan, dan Umbul Binangun. The income from tickets partly goes to the building maintainance The visitors management such as guiding, on the other hands performed by local people. This policy is taken in order to give positive impact to the surrounding community to improve their income The local people is able to earn extra income by working as a tour guide, selling refreshment and souvenir, providing services of photography, including up batik courses. Besides having positive impacts, the use of Tamansari as tourism object also lead to negative impacts. My observation result shows that visitors did vandalism. There are buildings that suffering severe damage due to vandalism.. I assume that this condition relates to the huge number of visitors without any good visitor management. To cope with this problems, it is necessary to provide proper visitor management at Tamansari. This study is aimed to design a proper visitor management concept. The concept is to maximize visitor experience and minimize any negative impact to the buildings. It can be gained by good cooperation between the owner (kraton), the government, both central and local government, academia, and the surrounding.communities